2020
DOI: 10.3847/1538-4357/ab917c
|View full text |Cite
|
Sign up to set email alerts
|

Observation and Modeling of High-temperature Solar Active Region Emission during the High-resolution Coronal Imager Flight of 2018 May 29

Abstract: Excellent coordinated observations of NOAA active region 12712 were obtained during the flight of the Highresolution Coronal Imager (Hi-C) sounding rocket on 2018 May 29. This region displayed a typical active region core structure with relatively short, high-temperature loops crossing the polarity inversion line and bright "moss" located at the footpoints of these loops. The differential emission measure (DEM) in the active region core is very sharply peaked at about 4 MK. Further, there is little evidence fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 82 publications
1
12
0
Order By: Relevance
“…This could imply the observation of emission from cospatial thermal components or, in the nonthermal interpretation, a situation in which loop-top flare-accelerated electrons are thermalized before reaching the loop footpoints (as was concluded in Glesener et al 2020). A similar lack of spatial complexity was also seen in the NuSTAR microflare examined in Glesener et al (2017), while, contrastingly, FOXSI HXR microflare emission was shown to be spatially complex in Vievering (2019). Further studies involving a greater number of HXR microflares of A class and below are necessary to determine the relative incidence of these two contrasting results and investigate if they are connected to other microflare properties.…”
Section: Discussionmentioning
confidence: 70%
“…This could imply the observation of emission from cospatial thermal components or, in the nonthermal interpretation, a situation in which loop-top flare-accelerated electrons are thermalized before reaching the loop footpoints (as was concluded in Glesener et al 2020). A similar lack of spatial complexity was also seen in the NuSTAR microflare examined in Glesener et al (2017), while, contrastingly, FOXSI HXR microflare emission was shown to be spatially complex in Vievering (2019). Further studies involving a greater number of HXR microflares of A class and below are necessary to determine the relative incidence of these two contrasting results and investigate if they are connected to other microflare properties.…”
Section: Discussionmentioning
confidence: 70%
“…Hydrodynamic models suggest a steady (high-frequency) heating (Winebarger et al, 2011) with loops close to equilibrium, satisfying the RTV scaling law (Rosner et al, 1978;Martens, 2010). This is supported partly by observations displaying very little intensity variability in the moss region (Warren et al, 2020), while other observations of active region cores provide evidence of strong variability, linked to either coronal nanoflares or magnetic flux cancellation events (Testa et al, 2014;Chitta et al, 2018;Tiwari et al, 2019).…”
Section: Active Region Core Loopsmentioning
confidence: 69%
“…The red contours mostly surround the bright moss emission in the AR core. Moss corresponds to the footpoints of high temperature (∼4 MK) loops ( 32 ). It means that plasma with the highest Si/S abundance ratios, a signature that is detected by Wind in the SEP events, is produced at the footpoints of the highest temperature loops in the AR.…”
Section: Resultsmentioning
confidence: 99%